2018
DOI: 10.1002/csr.1635
|View full text |Cite
|
Sign up to set email alerts
|

The effects of creating shared value (CSV) on the consumer self–brand connection: Perspective of sustainable development

Abstract: The purpose of this study is to shed light on the self–brand connection by analyzing two relationships: first, the effects on the self–brand connection of the association in a consumer's mind between the corporate strategy known as creating shared value (CSV) and brands that deploy this strategy; second, the effects on the self–brand connection of the association between corporate competence and brands. The paper examines whether the authenticity with which a firm deploys the CSV strategy (and markets products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 75 publications
(123 reference statements)
3
46
0
1
Order By: Relevance
“…The terms of loyalty is applied in diverse situations; therefore, the definition of loyalty differs depending on the situation. Recent studies of loyalty have used "a behavioral index, an attitudinal index, or a combined index incorporating behavioral, attitudinal, and cognitive aspects according to the nature of the research" [54][55][56]. From a behavioral perspective, loyalty can be determined only by purchase behavior with a focus on the outcome of such behavior.…”
Section: Brand Loyaltymentioning
confidence: 99%
See 1 more Smart Citation
“…The terms of loyalty is applied in diverse situations; therefore, the definition of loyalty differs depending on the situation. Recent studies of loyalty have used "a behavioral index, an attitudinal index, or a combined index incorporating behavioral, attitudinal, and cognitive aspects according to the nature of the research" [54][55][56]. From a behavioral perspective, loyalty can be determined only by purchase behavior with a focus on the outcome of such behavior.…”
Section: Brand Loyaltymentioning
confidence: 99%
“…From a behavioral perspective, loyalty can be determined only by purchase behavior with a focus on the outcome of such behavior. Brand loyalty is defined as "the likelihood of a customer repurchasing a certain product or service or recommending it to others; it is argued that customer loyalty results in continuous purchase behavior" [54][55][56][57][58]. For some scholars, brand loyalty refers to "a deeply held dispositional commitment that induces users to resist situational influences and marketing efforts that might have the potential to cause brand-switching behavior" [55,59].…”
Section: Brand Loyaltymentioning
confidence: 99%
“…The CSV strategy has important implications on companies' competitivity, on their behavior toward consumers and both the company's value and performance (Jin, 2018). Research carried out by Awale and Rowlinson (2014) on CSV effects on company competitivity has shown that CSV increases company competitivity through the improvement of its business and social conditions, an idea already brought to light by Porter and Kramer (2011).…”
Section: Review Of the Literature And Research Hypothesesmentioning
confidence: 99%
“…Authenticity is defined as "being genuine, real and true, instead of being fake, untruthful or hypocritical" (Jin, 2018(Jin, , p. 1249). Authenticity is defined as "being genuine, real and true, instead of being fake, untruthful or hypocritical" (Jin, 2018(Jin, , p. 1249).…”
Section: Csr-tax-related Inferential Mechanismsmentioning
confidence: 99%
“…The present study proposes that the positive halo effect of CSR engagement on perceived RTP is more pronounced the more consumers perceive firms' CSR engagement to be authentic and intrinsically motivated. Authenticity is defined as "being genuine, real and true, instead of being fake, untruthful or hypocritical" (Jin, 2018(Jin, , p. 1249). In the case of internal CSR engagement, which is focused on intraorganisational stakeholders and implies direct relationships between CSR engagement and the companies' processes and products and is thus less likely to produce moral capital (Godfrey, Merrill, & Hansen, 2009), sceptical inferences that might negatively influence the perceived tax behaviour are less likely to occur.…”
Section: Csr-tax-related Inferential Mechanismsmentioning
confidence: 99%